Molecular and morphological diversity of Rhizoctonia solani Kuhn inciting sheath blight disease in major rice growing areas of Southern Karnataka, India: Diversity of rice sheath blight pathogen in southern Karnataka - N. Kiran Kumar; M. K. Prasanna Kumar; Pooja S. Patel; T. Narendrappa (ORYZA-An International Journal of Rice, 2025)
Studies on morphological diversity of twenty Rhizoctonia solani isolates were carried out. The maximum and minimum hyphal widths of 7.21 and 3.45 µm was observed in MYRS 1 and HARS 1 isolates respectively. Highest mycelial growth of 54.8 mm was noticed in MYRS 3 and the least growth was observed in MYRS 2 (15.8 mm) 24 hrs after incubation. All the isolates were categorized based on different colony colours and sclerotial bodies produced except the isolate HARS 7. The latent period of the isolates to insight symptoms varied from 3 to 7 days and the genetic diversity showed good polymorphism using 19 ISSR markers. Among the 19 ISSR (Inter Simple Sequence Repeat) primers used, 16 primers yielded scorable and reproducible banding patterns which were selected for studying genetic variability. The 16 markers produced 128 band positions and all were polymorphic. The analysis resulted in description of entire population into five groups at 70 per cent dissimilarity coefficient.